Teicoplanin and vancomycin as treatment for glycopeptide-susceptible Enterococcus faecium bacteraemia: a propensity score-adjusted non-inferior comparative study - Yamaguchi, Ryo; Yamamoto, Takehito; Okamoto, Koh; Harada, Sohei; Echizenya, Miho; Tsutsumi, Takeya; Takada, Tappei (Journal of antimicrobial chemotherapy, 2023)
Abstract Objectives Limited evidence is available regarding alternative therapeutic agents to vancomycin in treating glycopeptide-susceptible Enterococcus faecium (GSEF) bacteraemia. This study assessed the effectiveness and safety of teicoplanin compared with vancomycin for treating GSEF bacteraemia. Patients and methods This was a retrospective, non-inferiority cohort study. Patients aged ≥18 years who developed GSEF bacteraemia and received either teicoplanin or vancomycin were included. The primary effectiveness outcome was the clinical success at the end of treatment, with a generalized linear model using the propensity score for selecting the agent as a covariate. We used an absolute difference of 20% in clinical success as the non-inferiority margin. Using multivariable logistic regression, the primary safety outcome was the incidence of acute kidney injury (AKI). Results In total, 164 patients (74 and 90 in the teicoplanin and vancomycin groups, respectively) were included. Overall, 64.9% (48/74) and 48.9% (44/90) of patients in the teicoplanin and vancomycin groups, respectively, achieved the primary effectiveness outcome. A generalized linear analysis showed an adjusted effectiveness difference of 9.9% (95% CI, −0.9% to 20.0%; P = 0.07), indicating non-inferiority of teicoplanin versus vancomycin. The incidence of AKI was 8.1% (6/74) and 24.4% (22/90) in the teicoplanin and vancomycin groups, respectively, with an adjusted OR of 0.242 (95% CI, 0.068 to 0.864; P = 0.029), indicating significantly lower AKI risk in the teicoplanin than in the vancomycin group. Conclusions Teicoplanin is a safe and useful alternative therapeutic agent for treating GSEF bacteraemia.